Estrogen Protects against Renal Ischemia-Reperfusion Injury by Regulating Th17/Treg Cell Immune Balance. (6th October 2022) - Zhang, Yang; Chang, Yuechen; Han, Ziwei; Ma, Ketao; Zeng, Xiansi; Li, Li
Abstract : Inflammation is a critical mediator of renal ischemia-reperfusion (I/R) injury (IRI), and T lymphocytes exert a key role in the renal IRI-induced inflammation. Connexin 43 (Cx43) is related to the maintenance of T lymphocyte homeostasis. Various preclinical researches have reported that estrogen is a renoprotective agent based on its anti-inflammatory potential. The present research is aimed at studying the role of T lymphocytes activated by Cx43 in 17 β -estradiol-mediated protection against renal IRI. Female rats were classified into six groups: control rats, I/R rats, ovariectomized rats, ovariectomized I/R rats, and ovariectomized rats treated with 17 β -estradiol or gap27. Levels of serum creatinine (Scr) and blood urea nitrogen (BUN) and Paller scoring were dramatically increased in I/R rats, especially in ovariectomized rats. By contrast, these indicators were markedly decreased by administering estradiol or gap27. Immunofluorescence staining revealed that CD4 + T cells infiltrated kidney tissues in the early stage of IRI. In both peripheral blood and renal tissue, the proportion of CD3 + CD4 + T cells and ratio of CD4 + to CD8 + were high in I/R rats, especially in ovariectomized rats. The proportion of CD3 + CD8 + T cells was low in peripheral blood but high in renal tissues. Administration of estrogen or Gap27 reversed these effects. IL-17 levels in both serum and tissue homogenate were significantly increased in ovariectomized rats subjected to I/R but significantly decreased in estrogen or gap 27 treated rats. The opposite trend was observed for IL-10 levels. Correlation analysis demonstrated that IL-17 was correlated positively with BUN, Scr, and Paller scores, while IL-10 was negatively correlated with these indicators. Western blot showed that Cx43 expression was markedly increased in the peripheral blood T lymphocytes of I/R rats, especially ovariectomized rats. After intervention with estrogen and gap27, Cx43 expression was significantly downregulated. These findings indicate that Cx43 may participate in the regulation of Th17/Treg balance by estrogen against renal IRI.